KOMBINASI SPEKTROFOTOMETRI ULTRAVIOLET DAN KALIBRASI MULTIVARIAT UNTUK ANALISIS SULFAMETOKSAZOL DAN TRIMETOPRIM SECARA SIMULTAN TANPA TAHAP PEMISAHAN - , Diana Silawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this study is to evaluate the capability of uvspectrophotometry in combination with multivariate calibration based on partial least square (PLS) regression for simultaneous quantitative analysis and dissolution evaluation of sulfamethoxazole (SUL) and trimethoprim (TRI) in tablet dosage form. The calibration and validation sample was constructed using 20 and 10 samples, respectively. The concentration range considered was 1-16 µg/ml for both SUL and TRI. Absorbance data of the calibration standards were taken between 200-400 nm. For achieving the best model, the related parameters of the model were evaluated. The optimum number of factors was selected by using the cross-validation method. The evaluation of calibration model is relied on the coefficient of determination (R 2 ), root mean square error of calibration (RMSEC), predicitve residual error sum of squares (PRESS) and root mean square error of cross validation (RMSECV). The coefficient of determination (R 2 ) for the relationship between actual values and predicted values was higher than 0.999 indicating good accuracy. The RMSEC values obtained were relatively low, i.e. 0.097 µg/mL (SUL) and 0.094 µg/mL (TRI) indicating good precision. Then, the difference between the actual and predicted value for each specimen is calculated. The sum of the squares of these differences is called the predicted residual error sum of squares (PRESS). The smaller the PRESS value, the better the predictive power of the model. The PRESS values obtained are 1.52 µg/mL (SUL) and 2.561 µg/mL (TRI). Then, the PRESS value used to determine RMSECV value, i.e. 0.269 µg/mL (SUL) and 0.358 µg/mL (TRI). The accuracy of developed method was comparable to that of HPLC. The developed method was succesfully used for quantitative analysis and dissolution studies of sulfamethoxazole and trimethoprim in tablet dosage form.